Emerging and Reemerging Virus Diseases of Vertebrates - Mahy, B.W.J. (Encyclopedia of Virology, 2008)
In the last two decades, a large number of new viruses have been discovered, many of which are pathogenic in humans or other vertebrates. Among the more important causes of virus emergence have been changes in human behavior, population, and increases in travel to distant countries. In addition, the application of new molecular technologies has led to the recognition of many viruses that hitherto went undetected. Many of the new, emerging viruses have an RNA genome, and many are zoonoses. The spread of human immunodeficiency virus, causing acquired immune deficiency syndrome, and the use of immunosuppressive drugs following transplant surgery, have increased the numbers of people in the population that are highly susceptible to emerging virus infections. The threat of a new pandemic of influenza virus in the human population stresses the need for development of better methods for detection, surveillance, and control of emerging virus diseases.